Evaluation of Patients with Vertigo by Cranial Magnetic Resonance Imaging (MRI) - Salih Hasan , Treefa (Diyala Journal of Medicine, 2021)
Background: Vertigo is a symptom that neurologists and otologists are confronted with. Magnetic resonance image (MRI) is used for imaging. Objective: To determine the diagnostic yield of MRI in patients with vertigo and to Identify the most common causes. Patients and Methods: This observational study involved 110 vertigo complaining patients attending the MRI unit of Rizgary teaching hospital examined by 0.2 Tesla MRI between June 2007 and September 2008.Collected variables divided into Group 1 (normal MRI) and Group 2 (abnormal MRI) analysed and compared. Results: Group 1= (70%) and Group 2=(30%), abnormal MRI findings in male patients was (59.6%), in female (40.4%,) the commonest abnormalities were cerebellopontine angle (CPA) space occupying lesions (SOL) (9.2%), cerebellar SOL (7.4%), 4th ventricle SOL (7.4%) and deep white matter ischemia (7.4%), most of patients with vascular problems were more than 50 years. In (35.4%) of patients, vertigo was less than one month duration, (50%) of which had abnormal MRI findings. Out of seven patients with normal MRI, 5 patients showed vascular lesion on magnetic resonance angiography (MRA). Conclusion: MRI remains important diagnostic tool for evaluation of vertigo and MRA is necessary when vascular origin is suspected.